AKHLAK DAN ETIKA - Mohammad Faizin (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2021)
As a scientific discipline, morality with ethics orients its study on human behavior in the perspective of how it should not be. So not a few among Muslims who translate morals with ethics. In fact, the two depart from a different study and from a different source. Morals are developed from standard Islamic sources, namely the Qur'an and Sunnah. While ethics is developed from the thinking of the human brain, namely philosophy, so that one is sacred and the other is profane, one is from heaven and the other is from earth, one is kholiq, while the other is from creatures. This thought feels unfair if moral behavior that is what it should be is based on ugliness, so that it becomes akhlakul qobiha or al akhlakul madmumah. Moreover, if morality is then believed to be an Islamic science, then of course the other Islamic sciences are fiqh, aqidah, and tasawwuf.